Improving Students’ Ability in Reading Comprehension Through Students Reading And Feedback At The Eighth Grade of SMP Negeri 3 Sogae’adu in 2022/2023 - Herman Syukur Zai; Kristof Martin; Afore Tahir Harefa; Hidayati Daeli (Journal on Education, 2023)
This research aims to improve students' abilities in reading comprehension by using the Reading and Feedback strategy. Researcher use Classroom Action Research (CAR). The subjects of this study were class VIII-A students of SMP Negeri 3 Sogae'adu for the 2022/2023 academic year, which consisted of 19 students. The researcher has conducted in two cycles. Each cycles consists of two meeting. In collecting the data, the researcher used observation sheet, test and field notes sheet. The result of the data in Cycle I, there were 7 students (37%) categorized in the fail level, 2 students ( 10 %) categorized into the less level, 3 students (16%) categorized into the adequate level, 7 students ( 37%) categorized into the good level. The average of the students’ value was 53.69%. This result showed that the students were unsuccessful. While in Cycle II, there were no students categorized into the fail, less and adequate level, 7 students (37%) categorized into the good level, and 12 students (63%) categorized into the very good level. The average of the students’ value was 83.68%. Therefore, the researcher concluded that the Students' Reading and Feedback (SRF) strategy was successful in improving students' reading comprehension ability in understanding recount text.